The GO-future and GO-past periphrases in Gallo-Romance: A comparative investigation - Paoli, S; Wolfe, S (Oxford University Press, 2022)
Investigating Gallo-Romance GO-past and GO-future periphrases, this chapter proposes that they originate from the same construction, in which the basic spatial meaning of GO is reinterpreted as temporal posteriority. Building on an intuition by Bres and Labeau (2013a) that the periphrasis itself is devoid of tense, the two temporal outcomes are derived through anchoring of the prospective movement to different reference frames: while the GO-past periphrasis is interpreted by anaphoric linking to the past events that surround it, the GO-future periphrasis is linked deictically to speech time. Assuming the same underlying construction for both periphrases and focusing on the component of posteriority has the advantage of maintaining the widely attested generalization that structures with verbs of motion grammaticalize into future grams.